From the cupboard to the boardroom and back: 100 plaster objects. (1st March 2015) - Bennett, Stuart
In 2013 the Dutch artist Krijn de Koning was invited to undertake a residency at Edinburgh College of Art (ECA). This resulted in an Edinburgh Art Festival co-commission, Land, in the Sculpture Court at ECA, his first work in the United Kingdom. During the fellowship Krijn and I worked with a group of students on a project centred around 100 small plaster objects that were donated by the estate of Eduardo Paolozzi to the School of Informatics at the University of Edinburgh in 2007. These models and casts were stored in cardboard boxes in a cupboard next to the Turing Room. In that room we unpacked the boxes and catalogued the objects in sketchbooks and photographs. The intention was to make the works public but what proved to be more intriguing were our discussions about the different senses of history and value we ascribed to the collection.